Beyond the Numbers: on the road to achieving public value in community support organisations - Fiona Girkin; Elizabeth Shannon; Craig Zimitat; Kate-Ellen Elliot (ACHSM, 2017)
Objective: To explore public value as a management tool for measuring outcomes, in Community Support Organisations (CSOs) and determine if further research is warranted. Design: A literature review on public value and outcome measurement in the community service sector was conducted to evaluate how public value best fits with CSOs. Setting: Public value has not previously been applied to measuring outcomes in CSOs and could provide beneficial information to assist in obtaining government funding as fiscal resources decline. Main outcome measures: The following question was considered; Can a public value framework be used as a management tool by CSOs to measure the value of their service? A flow chart applying a public value framework to outcome measurement of CSOs was developed. Results: Key elements identified were indicators, measures and outcomes. Stakeholders included; government, community sector, CSOs and consumer. A public value framework has the potential to be used for measuring outcomes in the community sector however realworld application is still required. Conclusion: This study provided preliminary application for a larger study and has provided evidence of a public value framework having the potential to be applied as an outcome measurement tool for CSOs. Abbreviations: CSO - Community Support Organisation